The valuable role of dynamic 18F FDG PET/CT-derived kinetic parameter Ki in patients with nasopharyngeal carcinoma prior to radiotherapy: A prospective study. (February 2023) - Huang, Xiaotao; Zhuang, Mingzan; Yang, Shuai; Wang, Ying; Liu, Qiaodan; Xu, Xiwei; Xiao, Mei; Peng, Yingpeng; Jiang, Ping; Xu, Wenhua; Guo, Shuanshuan; Wang, Rong; et al.
Highlights: Dynamic PET/CT offered the potential to improve the prediction and prognosis. K i derived from dynamic PET/CT reflecting the metabolism and biological activities of tissue. K i served as the complementary role of characterizing nasopharyngeal carcinoma. K i was potential to treat as a valuable imaging biomarker of NPC. Abstract: Background and Purpose: Dynamic positron emission tomography/computed tomography (PET/CT) served the potential role of characterizing malignant foci. The main objective of this prospective study was to explore the advantage of dynamic PET/CT imaging in characterizing nasopharyngeal carcinoma (NPC). Methods and Materials: Patients with probable head and neck disease underwent a local dynamic PET/CT scan followed by a whole-body static scan. Patlak analysis was used to generate parametric influx rate constant ( K i ) images from 48 frames obtained from a dynamic PET/CT scan. By delineating the volumes-of-interest (VOIs) of: primary tumor (PT), lymph node (LN), and normal nasopharyngeal tissues (N), we acquired the corresponding K i mean and SUVmean of each site respectively to perform the quantitative statistical analysis. Results: Qualified images of 71 patients with newly diagnosed NPC and 8 without nasopharyngeal malignant lesions were finally included. We found the correlations between K i mean-PT and critical clinical features, including clinical stage (r = 0.368), T category (r = 0.643) and EBV-DNA copy status (r = 0.351), and K i mean-PT differed within the group. SUVmean-PT showed correlations with clinical stage (r = 0.280) and T category (r = 0.472), but could hardly differ systematically within group of clinical features except T category. K i mean-LN offered the positive correlations with N category (r = 0.294), M category (r = 0.238) and EBV-DNA copy status (r = 0.446), and differed within the group. In addition, K i mean represented a sensitivity of 94.4 % and a specificity of 100 %, in distinguishing NPC from the non-NPC, when the cut-off was defined as 0.0106. When the cut-off of SUV being defined as 2.03, the sensitivity and specificity were both 100 %. Conclusion: Our research confirmed K i compared favorably to SUV in characterizing NPC and found that K i can serve as an effective imaging marker of NPC.